Conquered Populations in Early Islam Non-Arabs, Slaves and the Sons of Slave Mothers - Urban, Elizabeth (Edinburgh University Press, 2020)
This book traces the journey of new Muslims as they joined the early Islamic community and articulated their identities within it. It focuses on Muslims of slave origins, who belonged to the society in which they lived but whose slave background rendered them somehow alien. How did these Muslims at the crossroads of insider and outsider find their place in early Islamic society? How did Islamic society itself change to accommodate these new members? By analysing how these liminal Muslims resolved the tension between belonging and otherness, Conquered Populations in Early Islam reveals the shifting boundaries of the early Islamic community and celebrates the dynamism of Islamic history.